β-Caryophyllene Inhibits Oxaliplatin-Induced Peripheral Neuropathy in Mice: Role of Cannabinoid Type 2 Receptors, Oxidative Stress and Neuroinflammation - Jonathan Paulo Agnes; Barbara dos Santos; Raquel Nascimento das Neves; Vitória Maria Marques Luciano; Larissa Benvenutti; Fernanda Capitanio Goldoni; Roberta Giusti Schran; José Roberto Santin; Nara Lins Meira Quintão; Alfeu Zanotto-Filho (MDPI AG, 2023)
Peripheral neuropathy is an important adverse effect caused by some chemotherapeutic agents, including oxaliplatin (OXA). OXA-induced peripheral neuropathy (OIPN) is a challenging condition due to diagnostic complexities and a lack of effective treatment. In this study, we investigated the antiallodynic effect of β-caryophyllene (BCP), a cannabinoid type 2 (CB2) receptor agonist, in a mouse model of OIPN. BCP treatment inhibited OXA-induced mechanical and cold allodynia in both preventive and therapeutic drug treatment regimens. Experiments with the CB2 receptor agonist GW405833 confirmed the role of CB2 receptors in OIPN. The CB2 antagonist SR144528 abrogated the anti-nociceptive effect of BCP on mechanical allodynia, without impacting OXA-induced sensitivity to cold. BCP decreased neuroinflammation, as inferred from TNF, IL-1β, IL-6, and IL-10 profiling, and also reduced ROS production, lipid peroxidation, and 4-hydroxynonenal protein adduct formation in the spinal cords of OXA-treated mice. BCP did not affect the antitumor response to OXA or its impact on blood cell counts, implying that the cytotoxicity of OXA was preserved. These results underscore BCP as a candidate drug for OIPN treatment via CB2 receptor-dependent mechanisms, and anti-inflammatory and antioxidant responses in the spinal cord.